Hit & Myth David Nixon's A Midsummer Night's Dream and Swan Lake reviewed - Hutera, Donald (Dance Books Ltd., Alton,Hampshire (UK), 2004)
Northern Ballet Theatre. The lovers' encounters play like an extended chase scene propelled by breakneck lust. Nixon's third act plays like Swan on a Hot Tin Roof. PALABRAS CLAVE: David Nixon, A Midsummer Night's Dream, Swan Lake, Northern Ballet Theatre.